2010
DOI: 10.1002/stem.451
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells Are Capable of Executing G1/S Checkpoint Activation

Abstract: Embryonic stem cells progress very rapidly through the cell cycle, allowing limited time for cell cycle regulatory circuits that typically function in somatic cells. Mechanisms that inhibit cell cycle progression upon DNA damage are of particular importance, as their malfunction may contribute to the genetic instability observed in human embryonic stem cells (hESCs). In this study, we exposed undifferentiated hESCs to DNA-damaging ultraviolet radiation-C range (UVC) light and examined their progression through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 37 publications
(46 reference statements)
10
75
0
Order By: Relevance
“…While early work in mouse and human ESCs questioned the existence of functional G1-S restriction point [7,28], more recent data provided indirect evidence for activation of G1-S checkpoint in hESCs [9,10]. The distinction that we found between S-phase committed and non-committed G1 populations provides a strong support for this evidence.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…While early work in mouse and human ESCs questioned the existence of functional G1-S restriction point [7,28], more recent data provided indirect evidence for activation of G1-S checkpoint in hESCs [9,10]. The distinction that we found between S-phase committed and non-committed G1 populations provides a strong support for this evidence.…”
Section: Discussionsupporting
confidence: 68%
“…Initial work in embryonic stem cells (ESCs) hypothesized that this may not be applicable to ESCs because of their abbreviated G1 phase, which was thought to reflect lack of sensitivity to environmental cues [7,8]. This hypothesis, however, was later questioned by studies of human ESC (hESC) response to UV irradiation, which suggested the existence of a functional checkpoint [9]. The existence of G1 checkpoint in hESCs was further supported by expression of the hypophosphorylated form of the retinoblastoma protein (pRB) [10].…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have addressed the status of G1/S and G2/ M checkpoints responding to DNA damaging agents [14][15][16], the status of S-phase checkpoints in human ESCs is poorly understood. We show that, unlike somatic cells, human ESCs and EC cells fail to activate key S-phase checkpoint pathways that respond to replication stress and commit to apoptosis instead.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the strictness of the checkpoint is fully restored after the cells had begun differentiation. Thus, cells in the mouse embryo that have sustained DNA damage are rerouted to the differentiation pathway, ensuring the survival of the embryo at the expense of introduction of mutations, whereas human embryonic cells still must check for DNA damage in G1 phase and repair it within the time limits of the abbreviated G1 phase in order to be allowed to replicate their DNA [154][155][156]. Embryonic cells that have been temporarily trapped in G1 phase must either embark on the differentiation pathway, or else revert to apoptosis.…”
Section: Increasing the Propensity For Differentiation Along Multiplementioning
confidence: 99%